Financial services strategies in the euro-zone - Ingo Walter (EIB Papers, 1999)
Introduction of the euro certainly represents a sea-change in the environment of modern global finance. In the three decades since the end of the Bretton Woods system in 1971, and against great odds, Europe has forged a platform that could ultimately emerge as a viable challenger to the United States as the world's premier financial market. It was a difficult birth - but if ever the saying 'no pain, no gain' applies in context of macro-financial reform, this is it (1). Financial institutions are extraordinarily sensitive even to small changes in the environment. Increases in interest-rate or exchange-rate volatility can create wholly new markets for riskmanagement products, just as surely as these businesses - often built-up at huge expense - can be wiped-out overnight if volatility drops. Regulatory concerns about counterparty or liquidity risk in over-the-counter (OTC) markets can quickly drive transactions onto organised exchanges and their standardised contracts, and eliminate much of the innovation that is most easily undertaken in interprofessional OTC markets. Similar stories could be related to changes in tax codes, transactioncosts, information technologies, and an array of other variables that form the environmental overlay of business strategy in the financial services industry. These are parameters that management has to carefully think through, build a consensus on, and then place its strategic bets. When mistakes are made in devising core strategies in the financial services industry, they are usually big ones.
Keywords: 330; Finanzdienstleistung; Euro; Euromarkt; EU-Staaten; Internationale Bank